PROPOSAL FOR STEM EDUCATION COMPETENCY FRAMEWORK FOR PRIMARY EDUCATION UNIVERSITY STUDENTS ACCORDING TO CDIO APPROACH - Nguyen Thi Phuong Nhung (Tạp chí Khoa học, 2025)
In the context of fundamental and comprehensive general education reform in Vietnam, STEM education competence among primary school teachers has become an urgent requirement to meet the demands of 21st-century student development. This study proposes a STEM education competency framework for students majoring in Primary Education, following the CDIO approach, aiming to guide curriculum development and assess the practical competencies of future teachers. Based on a synthesis of theoretical foundations, analysis of current conditions, and expert consultation using a two-round Delphi method (n=12), the research team developed a competency framework comprising five main domains: (1) STEM awareness and thinking; (2) Designing STEM educational activities; (3) Implementing STEM educational activities; (4) Applying technology and engineering in STEM education; and (5) Evaluating and improving STEM educational activities. Each competency domain includes two specific evaluation criteria, described across four developmental levels from basic to advanced. Expert evaluations indicate a high level of relevance and feasibility, affirming the framework's potential for application in training and assessing primary teacher education students with an emphasis on integrated and practical education.